2021
DOI: 10.3390/agriculture11010060
|View full text |Cite
|
Sign up to set email alerts
|

Earthworm Inoculation Improves Upland Rice Crop Yield and Other Agrosystem Services in Madagascar

Abstract: The effects of earthworm inoculation and cropping systems on upland rice systems were examined over a four-year period in the Highlands of Madagascar. Each year, endogeic earthworms Pontoscolex corethrurus (Rhinodrilidae) were inoculated (EW+) at a density of 75 ind m−2 or were not inoculated (EW0). Inoculation was tested in three cropping systems: conservation agriculture (CA) and traditional tillage with or without residues restitution. Soil and plant properties were measured during the first three years whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 46 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Numerous previous studies have shown that earthworm inoculation increases the yield of spinach [43], peanut [44], upland rice [26], rainfed rice [27,28] and other crops. However, only Liang et al confirmed the effect of earthworm inoculation on irrigated rice yield increasing through the rice ridge planting experiment [29].…”
Section: Earthworm Inoculation Improved Irrigated Rice Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous previous studies have shown that earthworm inoculation increases the yield of spinach [43], peanut [44], upland rice [26], rainfed rice [27,28] and other crops. However, only Liang et al confirmed the effect of earthworm inoculation on irrigated rice yield increasing through the rice ridge planting experiment [29].…”
Section: Earthworm Inoculation Improved Irrigated Rice Growthmentioning
confidence: 99%
“…Studies have shown that inoculation of earthworms in dryland ecosystems can improve physical properties [11,12], chemical properties [13,14] and biological properties [15,16] of soil, accelerate the decomposition of soil pollutants [17], reduce heavy metal activity [18] and promote crop growth [19][20][21]. However, studies on the symbiotic relationship between earthworms and rice are mainly concentrated in the laboratory [22,23], upland paddy fields [24][25][26] or rainfed paddy fields [27,28]; studies under irrigated paddy fields are scarce with the exception of Liang et al [29]. The biggest technical difficulty is that the traditionally irrigated paddy environment during rice planting is not suitable for the growth of earthworms.…”
Section: Introductionmentioning
confidence: 99%